2019
DOI: 10.1111/anu.13002
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth, plasma hormones and metabolites in juvenile Siberian sturgeon ( Acipenser baerii , Brandt 1869) subjected to fasting and re‐feeding

Abstract: A 7‐week study was conducted to investigate the effect of different fasting and re‐feeding regimes on compensatory growth and some physiological parameters of juvenile Siberian sturgeon (Acipenser baerii). Fish (46.5 ± 0.5 g) were fed on a diet (containing 450 g/kg crude protein and 20 MJ/kg digestible energy) according to four feeding regimes in triplicate including: control group (C, fed everyday), W1 (2 weeks of feeding followed by 1 week of fasting and 4 weeks of re‐feeding), W2 (1 week of feeding followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Furthermore, starvation of L. rohita for a week pronouncedly elevated serum ALT and AST in the gills and the liver, but their levels significantly decreased after a week of RF. Ashouri et al (2020) demonstrated that levels of AST, ALP, and LDH in plasma juvenile Siberian sturgeon (Acipenser baerii) were subjected to one, two, and three weeks of FA were increased, but their values restored to normal ranges after four weeks of RF. The activity of ALT in the liver of A. latus in T2 increased, suggesting elevation amino acids mobilization for providing energy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, starvation of L. rohita for a week pronouncedly elevated serum ALT and AST in the gills and the liver, but their levels significantly decreased after a week of RF. Ashouri et al (2020) demonstrated that levels of AST, ALP, and LDH in plasma juvenile Siberian sturgeon (Acipenser baerii) were subjected to one, two, and three weeks of FA were increased, but their values restored to normal ranges after four weeks of RF. The activity of ALT in the liver of A. latus in T2 increased, suggesting elevation amino acids mobilization for providing energy.…”
Section: Discussionmentioning
confidence: 99%
“…Restocking programs are also of great interest for this species since it is included in the list of endangered wild populations 1 . Compared to other sturgeon species, Acipenser baerii shows rapid growth rate, resistance to pathogens, a relatively short reproductive cycle (7–8 years) and can be reared using a wide range of diets and environmental conditions 2 , 3 . Owing to its features and high commercial value, intensive aquaculture of Siberian sturgeon is presently carried out in different parts of the world and, in recent years, several studies regarding farming-related biology 4 and nutritional requirements 1 , 5 have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmatic glucose levels is a routine index to determine nutritional status (Pottinger et al, 2003) and nutritional stress (Furné et al, 2012;Pérez-Jiménez et al, 2012). It is noteworthy that the maintenance of this metabolite during fasting has been reported for other fish species (Ashouri et al, 2019;Bermejo-Poza et al, 2019;Mozanzadeh et al, 2015;Yarmohammadi et al, 2012), which reveals the capacity and plasticity of some fish species in the face of short-term fasting. In general, serum glucose are maintained by glycogenolysis (the break of glycogen in the liver by gluconeogenesis), generating glucose from lactate, amino acids and glycerol (Favero et al, 2019;Ashouri et al, 2019).…”
Section: Glycemic Activity and Hepatic Aminotransferasesmentioning
confidence: 93%
“…Several studies demonstrated that teleost fish are capable of tolerating periods of unfavorable feeding conditions by activating behavioral changes and biochemical, physiological and structural adaptive responses (Ashouri et al, 2019;Mozanzadeh et al, 2015). Fish have the ability of reducing their energy costs in fasting periods and reusing proteins (Salem et al, 2007).…”
Section: Glycemic Activity and Hepatic Aminotransferasesmentioning
confidence: 99%
See 1 more Smart Citation